PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PENCABULAN DI POLRESTA BUKITTINGGI - Yuserlina, Anny; Failin, Failin; Basir, Gusril (Ensiklopedia of Journal, 2025)
Children are the young generation as one of the human resources who are the potential and successor to the ideals of the nation's struggle, who have a strategic role and have special characteristics and characteristics, require guidance and protection to ensure complete, harmonious physical, mental and social growth and development, harmonious and balanced and in order to be guaranteed from acts of violence, very optimal and special legal protection is needed so that victims of criminal acts of sexual abuse against children receive appropriate legal protection as their rights must be fulfilled. The legal protection given to children as victims of criminal acts of sexual abuse at the Bukittinggi Police is a legal protection provided by the state/government, law enforcement officers who handle cases concerning children. Efforts to provide legal protection for children who are victims of sexual abuse have been made in such a way, starting from providing assistance to the victim to developing the mental state of the victim as a result of the sexual abuse incident they experienced. Several efforts are made by the police to protect children, namely keeping the victim's identity secret, providing rehabilitation efforts, providing protection and assistance during the investigation, prosecution and trial process, as well as obtaining information about the progress of the trial. However, legal handling efforts carried out by law enforcement officers in cases of criminal acts of sexual abuse in which children are victims are still not optimal.Keywords:  Legal Protection, Children, Crime, Obscenity